2022
DOI: 10.3762/bjoc.18.20
|View full text |Cite
|
Sign up to set email alerts
|

Multi-faceted reactivity of N-fluorobenzenesulfonimide (NFSI) under mechanochemical conditions: fluorination, fluorodemethylation, sulfonylation, and amidation reactions

Abstract: In the search for versatile reagents compatible with mechanochemical techniques, in this work we studied the reactivity of N-fluorobenzenesulfonimide (NFSI) by ball milling. We corroborated that, by mechanochemistry, NFSI can engage in a variety of reactions such as fluorinations, fluorodemethylations, sulfonylations, and amidations. In comparison to the protocols reported in solution, the mechanochemical reactions were accomplished in the absence of solvents, in short reaction times, and in yields comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Especially, mechanochemistry enabled fluorination of C( sp 3 )−H bond in enolizable substrates utilizing electrophilic fluorinating reagents under solvent‐less conditions [5h,i,j] . A recent report demonstrated that mechanochemical fluorination of aromatic C( sp 2 )−H bond is feasible using N ‐fluorobenzenesulfonimide (NFSI) as the fluorinating agent [13] . However, to date, no mechanochemical fluorination process for unactivated C( sp 3 )−H bonds has been reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, mechanochemistry enabled fluorination of C( sp 3 )−H bond in enolizable substrates utilizing electrophilic fluorinating reagents under solvent‐less conditions [5h,i,j] . A recent report demonstrated that mechanochemical fluorination of aromatic C( sp 2 )−H bond is feasible using N ‐fluorobenzenesulfonimide (NFSI) as the fluorinating agent [13] . However, to date, no mechanochemical fluorination process for unactivated C( sp 3 )−H bonds has been reported.…”
Section: Methodsmentioning
confidence: 99%
“…[5h,i,j] A recent report demonstrated that mechanochemical fluorination of aromatic C(sp 2 )À H bond is feasible using N-fluorobenzenesulfonimide (NFSI) as the fluorinating agent. [13] However, to date, no mechanochemical fluorination process for unactivated C(sp 3 )À H bonds has been reported. Inspired by the recent development of the hydrogen atom transfer (HAT)mediated CÀ H functionalization reactions, [14] we, here-in, present a mechanochemical process for fluorinating unactivated CÀ H bonds utilizing the HAT reaction of the N-centered radical species generated from the readily available NFSI.…”
mentioning
confidence: 99%
“…6,7 Recently, solid-state mechanochemical synthesis using ball milling has attracted increasing attention as an alternative and efficient synthetic approach. [8][9][10][11][12][13] Solid-state conditions allow the reactions to be conducted under solvent-free conditions and at high concentrations, which would provide new synthetic solutions in conjugated molecular synthesis. [14][15][16][17] Some solid-state palladium-catalyzed Suzuki-Miyaura crosscoupling reactions by ball milling have been reported for preparing functional conjugated materials.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, solid-state mechanochemical synthesis using ball milling has attracted increasing attention as an alternative and efficient synthetic approach. 8–13 Solid-state conditions allow the reactions to be conducted under solvent-free conditions and at high concentrations, which would provide new synthetic solutions in conjugated molecular synthesis. 14–17…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated how, depending on the azobenzene structure, the halogenation of the C–H bonds with NBX occurred in the presence of Pd(II) catalysts or under metal-free conditions ( Scheme 1b ). Similarly, in the absence of metal catalysts, N -fluorobenzenesulfonimide (NFSI) was found to act as a mild fluorinating reagent for activated aromatics by mechanochemistry [ 5 ]. Such a collective effort to access halogenated substrates is understandable, owning the synthetic value of organic halides as substrates in multiple reactions.…”
mentioning
confidence: 99%